Postnatal development and distribution of sympathetic innervation in mouse skeletal muscle - Straka, Tatjana; Vita, Veronica; Prokshi, Kaltrina; Hörner, Sarah J.; Khan, Muzamil Majid; Pirazzini, Marco; Williams, Marion Patrick Ivey; Hafner, Mathias; Zaglia, Tania; Rudolf, Rüdiger (International journal of molecular sciences, 2018)
Vertebrate neuromuscular junctions (NMJs) have been conceived as tripartite synapses composed of motor neuron, Schwann cell, and muscle fiber. Recent work has shown the presence of sympathetic neurons in the immediate vicinity of NMJs and experimental and clinical findings suggest that this plays an eminent role in adult NMJ biology. The present study examined the postnatal development and distribution of sympathetic innervation in different muscles using immunofluorescence, confocal microscopy, and Western blot. This demonstrates the proximity of sympathetic neurons in diaphragm, extensor digitorum longus, tibialis anterior, soleus, and levator auris longus muscles. In extensor digitorum longus muscle, sympathetic innervation of NMJs was quantified from perinatal to adult stage and found to increase up to two months of age. In diaphragm muscle, an extensive network of sympathetic neurons was prominent along the characteristic central synapse band. In summary, these data demonstrate that an elaborate sympathetic innervation is present in several mouse skeletal muscles and that this is often next to NMJs. Although the presence of sympathetic neurons at the perisynaptic region of NMJs increased during postnatal development, many synapses were already close to sympathetic neurons at birth. Potential implications of these findings for treatment of neuromuscular diseases are discussed.